NOx REDUCTION BY ADSORPTION AND HYDROGEN-SELECTIVE CATALYTIC REDUCTION USING Pt-ZEOLITE : PART I. SPECTROSCOPIC STUDY AND EFFECT OF TEMPERATURE TO ACTIVITY - Fatimah, Is; Hidayat, Arif (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
In this paper, spectroscopic investigation on NOx adsorption and Hydrogen- Selective Catalytic Reduction (H-SCR) by using Pt-zeolite and also study on the effect of temperature to the % activity of reduction are presented. FTIR and UV-Visible spectro-photometry reveal the chemisorption occure during NOx adsorption by Pt-zeolite. Fur-thermore in the effect of temperature study, it concluded that both of processes significantly affected by temperature. Arrhenius model is used to predict this effect and the result show that activation energy of NOx reduction in H-SCR system is 0.2640 Joule/mol and adsorption energy is 4.0617 Joule/mol.